2003
DOI: 10.1034/j.1399-3038.2003.00040.x
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of sesame sensitivity among infants and children

Abstract: Recently, we found sesame to be a major cause of severe IgE-mediated food allergic reactions among infants and young children in Israel. The purpose of this study was to describe the different patterns of sesame sensitivity. We have identified three subgroups among our patients (n = 32). Group I (n = 23, M/F; 14/9) consisted of cases with IgE-mediated sesame allergy. The mean age of the first allergic reaction was 11.7 months. Although the main clinical manifestation was urticaria/angiedema (n = 14, 60%), anap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 11 publications
(14 reference statements)
2
26
1
Order By: Relevance
“…The present study did not reveal any factors associated with FA, although previous studies have suggested risk factors for the development of FA such as a family history of atopic disease, birth season, and the early ingestion of allergenic foods 6,26,27. However, this study had a limitation in assessing risk factors of FA, because our survey did not include questions on aspects including family history, which is known to be related to atopic diseases.…”
Section: Discussioncontrasting
confidence: 62%
“…The present study did not reveal any factors associated with FA, although previous studies have suggested risk factors for the development of FA such as a family history of atopic disease, birth season, and the early ingestion of allergenic foods 6,26,27. However, this study had a limitation in assessing risk factors of FA, because our survey did not include questions on aspects including family history, which is known to be related to atopic diseases.…”
Section: Discussioncontrasting
confidence: 62%
“…There are a few cases in the literature of immediate hypersensitivity to sesame seed with negative skin prick test and/or IgE antibody test results that were confirmed by oral challenge tests [7]. In one study of sesame seed allergy in children, immediate reaction to a minimal amount of sesame was characteristic; skin was the most common site of involvement, followed by respiratory and gastrointestinal systems; tolerance developed in only 20% of the patients, and high sIgE (> 0.15 IU) was demonstrated only in 75% of those in which it was examined [8].…”
Section: Discussionmentioning
confidence: 99%
“…Another study described 9 of 30 children (30%) developing tolerance at an average age of 2.8 years 3. Dalal et al reported anaphylaxis as the presenting symptom in 30% of children with sesame allergy, all occurring in patients less than 1 year of age 4. This is of significant clinical concern in children who are too young to describe their symptoms.…”
Section: Introductionmentioning
confidence: 99%